The Foreign Policy of Russia and the United States of America in the South Caucasus Region (2004-2024) - Daniyal Rezapour (The Review of International Affairs)
The Caucasus region has received less attention from Eurasian scholars and policymakers in recent years due to the ongoing armed conflict in Ukraine and the turmoil in the West Asian region. However, the Caucasus region, especially the South Caucasus, suffers from severe geopolitical fragility due to internal and external reasons. As the post-Cold War rivalry between Russia and the United States has reached its highest point, their process of engagement and competition in this sensitive part of Eurasia deserves attention. Therefore, while examining the bilateral relations between Moscow and Washington in the Caucasus, the author aims to explain the current situation in the region and the logic of cooperation and competition between the two countries in recent years. The main objective of this research is to answer the question of what policies the United States and Russia have adopted towards the crises in this region and the reasons and logic of these two countries for these policies. The hypothesis put forward in response to this main question is that different perceptions of how to gain strategic, security, and military benefits have led to the competitive policymaking of Russia and the United States in the crises of the Caucasus region. This research also focuses on the cooperative logic of the United States and Russia in relation to the processes of resolving ethnic and political conflicts in Abkhazia, South Ossetia, and Nagorno-Karabakh, which is in line with preserving the perceptual structure of the international system. While relying on the theory of attribution error and the descriptive-analytical approach to examine these hypotheses, the study method is based on documentary research using library data collection and analysis, websites, articles, and Internet resources.